The Role of Work Experience, Work Discipline, Information Technology, and Training on The Performance of Police Members - Cahyono, Natalena Eko; Istiatin, Istiatin; Surdawarti, Surdawarti (Universitas Pamulang, 2025)
This research aims to determine the influence simultaneously (simultaneously) and partially of the variables of work experience, work discipline, information technology, and training on the performance of members of the Binkar SSDM Bureau of the South Jakarta Police. This research method uses a quantitative research design. The population of all employees/members working at the Binkar SSDM Bureau of the South Jakarta Police is 220 people. The sampling technique used in this research was a purposive sampling technique with a sample size of 55 respondents. Data collection using questionnaires. The data analysis techniques used for statistical analysis are multiple linear regression test, F test, t test, and coefficient of determination. The research results show that work experience, work discipline, information technology and training partially and significantly influence the performance of members of the South Jakarta Police Binkar SSDM Bureau. Suggestions from this research, the South Jakarta Police SSDM Binkar Bureau continues to improve work experience, work discipline, information technology and existing training, so that the performance of members will increase and be better than before.